Desafios à permanência e agendas de acolhimento no mestrado profissional: um estudo com trabalhadores pesquisadores - Vieira, Karen Mariane Petry Welter (2022)
This research main focus is on the challenges and vulnerability faced by Professional Master’s Degree students while they are attending their course at the Postgraduation Program for Public Policies and Educational Management (Programa de Pós-graduação em Políticas Públicas e Gestão Educacional). The investigation is focused on researchers who also have to work (working researchers) and based on their experience, it is intended to develop a Welcoming Program for Postgraduation courses. A Welcoming Program for Postgraduation refers to the institutional policies created to help with the permanence of working researchers, which are consisted of a projection of a series of actions and procedures in order to strengthen the qualification of the professionals who are in this academic context. This implicated and applied study is part of the Line of Research (LS) 2: Pedagogical Maganement and Educational Contexts (Gestão Pedagógica e Contextos Educativos) of the Professional Master’s Degree in Public Policies and Educational Management (MP/PPPG). This study is also result of the Group of Research, Practices and teaching formation: basic and higher education (Grupo de Pesquisa, Práticas e formação para a docência: educação básica e superior (GPDOC)) at the Federal University of Santa Maria (Universidade Federal de Santa Maria (UFSM)), which has investigated subjects related to school management, professional development and formation, emergent contexts and social vulnerability. Since the social, cultural and political conditions that are part of our society are also present in the academic context, which reveals challenges and tension for working researchers on their formative process, the discussion about vulnerabilities in the postgraduation academic context are considered relevant. Because of this, the research question asks: what vulnerabilities and challenges do the working researchers at the Professional Master’s Degree of the Public Policies and Educational Managem Postgraduation Program face? Besides understanding the vulnerabilities and challenges that are part of the working researchers academic life in order to develop a Welcoming Program for postgraduation students, it is also aimed to recognize what conditions make the permanence and success of the Professional Master’s Degree students vulnerable, to identify indicators of postgraduation permanenceto and to discuss about possible actions for the creation of a Welcoming Program for the Professional Master’s Degree students/researchers. A qualitative approach of sociocultural perspective study was used to conduct the research, which included the use of questionnaires and conversation circles. The conversation circles were organized based on four main steps: listening, contextualization, experimentation and re-elaboration. In addition, the subjects of this research were the students/researchers who started the MP/PPPG in 2019 and 2020. As a result, the challenges and vulnerabilities identified during the Professional Master’s Degree course attendance were the lack of time as a consequence of work responsibilities, gender issues, social distancing because of COVID-19 and difficulties on finding information about the Postgraduation Program. The indicators of Postgraduation permanence were the institutional support, the social relationship with colleagues and advisor, the possibility of not attending work to be able cope with Postgraduadion demands and requirements, which are worker-oriented. In conclusion, the product of this investigation are indicators that enable a Welcoming Program for the Professional Master’s students, intended to enhance students formative period.